Silencing grievance: Responding to human rights violations in Mexico’s war on drugs - Trevino-Rangel, Javier (2018)
Scholarly studies addressing the issue of human rights abuses in Mexico’s war on drugs could be classified into two groups. A first cluster of literature addresses the deployment of legal dispositions that allow the commission of human rights abuses. A second analyzes the consequences of such political or legal dispositions—for example, the use of torture. However, to increase our understanding of Mexico’s human rights crisis, a third analysis is needed: the study of the official discourse that authorizes such disturbing legal dispositions and its effects. This article is a sociologically-driven analysis of the government responses to human rights abuses between 2007 and 2012. The Calderón administration deployed what can be termed the policing of uncomfortable truths, which served to deny or justify the occurrence of atrocity. The article also suggests the effects such policy had in victims of abuses, perpetrators, and bystanders of atrocity